2015
DOI: 10.1161/strokeaha.115.008836
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Wall Shear Stress of Cerebral Arteriovenous Malformation Feeder Arteries After Embolization and Surgery

Abstract: Background and Purpose— Wall shear stress (WSS) has been implicated as an important stimulus for vascular remodeling. The purpose of this study is to measure WSS in AVM arterial feeders using quantitative magnetic resonance angiography pre- and post-embolization/surgery. Methods— Records of patients who underwent AVM embolization and surgical resection at our institution between 2007 and 2013 and had WSS, flow rate, and vessel diameter obtained pre- and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 20 publications
0
22
1
Order By: Relevance
“…17 More recently, Alaraj et al demonstrated that WSS was a potential biomechanical factor for efficient treatment of arteriovenous malformations. 1 In the present study, the mean WSS of both surgical and nonsurgical ICAs decreased, with the difference in mean WSS between surgical and contralateral ICAs following surgery found to be not significant. Because multiple stenotic changes occur along the ICA, the mean WSS may not be a sensitive parameter in the measurement of hemodynamic changes following surgery for treatment of MMD.…”
Section: Discussioncontrasting
confidence: 58%
“…17 More recently, Alaraj et al demonstrated that WSS was a potential biomechanical factor for efficient treatment of arteriovenous malformations. 1 In the present study, the mean WSS of both surgical and nonsurgical ICAs decreased, with the difference in mean WSS between surgical and contralateral ICAs following surgery found to be not significant. Because multiple stenotic changes occur along the ICA, the mean WSS may not be a sensitive parameter in the measurement of hemodynamic changes following surgery for treatment of MMD.…”
Section: Discussioncontrasting
confidence: 58%
“…However, the system is limited with respect to achieving a completely physiological flow rate and shear stress level, which was limited by the ability of the endothelial cells to adhere to the artificial collagen substratum. Average WSS measurements lie in the range of 2 -67.4 dynes/cm 2 for the large cerebral feeder vessels of AVMs [37], and in the range of 7 -23 dynes/cm 2 for normal intracranial vessels [38]. The ability to culture human AVM endothelial cells isolated from surgically excised human AVMs would also be more physiologically relevant but we consider not necessary for early development and pre-testing of conjugate once a valid target is identified.…”
Section: Plasma Fdp Levelmentioning
confidence: 99%
“…Alternatively, we also have uncertainty of posttherapeutic ICH, such as after microsurgical, embolization, or gamma knife treatments . Demonstrating flow parameters preintervention that elevate posttreatment risk could help direct patients to alternative therapies and/or different postsurgical management . Research into both of these clinical scenarios has enlisted hemodynamic metrics to help explain such hemorrhagic episodes with varying degrees of success.…”
Section: Alteration Of Hemodynamics Exacerbates Bavm Hemorrhagementioning
confidence: 99%